Use of Imogene King´s Nursing Model in the Care for a Patient with Heart Arrhythmias - Chloubová, Iva; Bulava, Alan (Magyar Egészségügyi Szakdolgozói Kamara, 2019)
The aim of this work was to find out advantages of Imogene King´s model in nursing care in patients with heart arrhythmias to find out how patients are limited to saturation of their own needs and in which areas the most severe limitations occur in patients with heart arrhythmias.
Keywords: nurse; nursing model; quality of liffe; arrhythmia